Optimization of the Position for the Support To Reduce Production Time on 3D Printers - Nghi Huynh, Huu; Nguyen Thanh, Ha; Tho Nguyen, Huu; Thu Ha Thai, Thi (International Journal of Engineering and Technology, 2018)
FDM (Fused Deposition Modeling) is the AM - Additive Manufacturing Technology or the fastest growing 3D printing technology has been paid more attention in Vietnam. Although this technology is being used in important fields such as industry, medicine, aerospace and education, etc. but product quality and manufacturing time are still the main limitation for its popularity. There are many factors which influence the fabrication time. In particular, the structure of the support part is one of the important factors. This paper examines the influence of technological parameters such as the direction of prototyping, the distance between the support and the material layer, and the location of support in order to reduce production time based on open source FDM devices. Besides, the study also uses the Taguchi method to design experiments and analyze the variance (ANOVA) to evaluate the effect of technological parameters on fabrication time. From obtained results, the optimal parameter values and the relationship function of the parameters have been figured out.Â Â